Blood cockle (Anadara granosa) supplementation to increase serum calcium level and femur growth of low-protein diet rat - MARGARETHA SOLANG (Smujo International, 2017)
Solang M. 2017. Blood cockle (Anadara granosa) supplementation to increase serum calcium level and femur growth of lowprotein diet rat. Nusantara Bioscience 9: 62-67. Blood cockle (Anadara granosa) contains protein, zinc and calcium. The aim of this study was to evaluate the effects of blood cockle flour supplement on serum calcium level, rat femur length and weight of rat femur on low-protein diet. The design of research used The Separate Sample Pre-Post Test Design. Forty eight Wistar male rats were randomly grouped into 2 groups, 12 rats as normal control group and 36 rats as malnourished group. After eight weeks, 4 rats from each group were sacrificed. Furthermore, 8 rats as normal control and 32 rats as malnourished group were randomly grouped. Malnourished rats were treated with blood cockle flour of 12.5%/kg diet, 25%/kg diet, and 50%/kg diet ad libitum for 8 weeks. Data analysis was performed with One Way ANOVA, LSD, Kruskal-Wallis and Mann-Whitney tests. The results of study showed that the supplementation of blood cockle flour of 12.5%/kg diet was significantly increase the serum calcium level (p=0.003), rat femur length (p=0.000) and rat femur weight (p=0.002) on low-protein diet. This study demonstrated that blood cockle flour can be used as alternative food to improve the growth of rat femurs in a malnutrition condition.